The National Idea of the Serbs in 1914: Curiosity and/or Destiny? - Marković, Saša S. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
The development of the Serbian national idea is a layered, complex, and historically enduring phenomenon. It consists of a palimpsest of numerous ideas shaped at various moments throughout the struggle for liberation and state formation. Each layer reflects a distinct approach in which rational thought intertwines with the overwhelming power of emotions. Patriotism is often inspired by a romanticized representation of the past. Through the adoption of education, the national idea could have become more grounded in reality, but the will to realize such an ambitious project was lacking. Conversely, it risked becoming increasingly imaginaryguided by idealized notions yet ultimately overwhelmed by complex realities. At times, this idea fostered genuine self-confidence; at others, mere self-assuredness. The line between the two is often blurred, and an exclusive reliance on either may have hindered national development. The way out of this contradiction lies in confronting the Serbian national idea and its manifestations without ideological biasneither glorifying nor denying it.